hydratiion characteristics and strenght properties of cement bonded concrete composites reinforced with particles of tectona grandis wood and waste polyethylene terephthalate bottles (2018)
particles of of waste polyethylene terephthalate bottles (PET)and tectona grandis were tested in compactibility in cement bonded composite production using hydration approach . The fabricated cements bonded concretes bonded composites from the PET and T. grandis particles and thier mixtures was compatible with cement having maximum hydration temperature (Tmax) of 47.0-50.6 oC, maximum hydration time (Tmax) of 7.9-8.0h and temperature dependent ratio index(tR) of 0.9. the flexural properties i.e moduli of rupture and elasticity were between 7.2 and 45.9 N/mm2 and 653.1 and 1612.4 N/mm2.the fabricated composites are suitable for use as low-cost building components.